2023
DOI: 10.1002/ctm2.1203
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell transcriptomic analysis deciphers key transitional signatures associated with oncogenic evolution in human intramucosal oesophageal squamous cell carcinoma

Abstract: Background and aims The early diagnosis and intervention of oesophageal squamous cell carcinoma (ESCC) are particularly important because of the lack of effective therapies and poor prognosis. Comprehensive research on early ESCC at the single‐cell level is rare due to the need for fresh and high‐quality specimens obtained from ESD. This study aims to systematically describe the cellular atlas of human intramucosal ESCC. Methods Five paired samples of intramucosal ESCC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
(105 reference statements)
0
5
0
Order By: Relevance
“…By contrast, the immune system faces possible collapse due to the tumor invasion. 45 The CD4+ T lymphocyte number usually decreases significantly. Therefore, immune monitoring for cancer patients can provide important indications for cancer treatment planning and prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, the immune system faces possible collapse due to the tumor invasion. 45 The CD4+ T lymphocyte number usually decreases significantly. Therefore, immune monitoring for cancer patients can provide important indications for cancer treatment planning and prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…We identified TREM2 Macro as a critical mediator of tumor progression through MDK-related communications, especially the MDK-NCL axis. Other studies have indicated that tumor cells confer a malignant phenotype to other cells through the MDK-NCL axis and alter the TME to promote angiogenesis and cancer metastasis 27–29 . This suggests that malignant cells directly recruit TREM2+ macrophages to the TME, contributing to a more aggressive tumor phenotype.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies have indicated that tumor cells confer a malignant phenotype to other cells through the MDK-NCL axis and alter the TME to promote angiogenesis and cancer metastasis. [27][28][29] This suggests that malignant cells directly recruit TREM2+ macrophages to the TME, contributing to a more aggressive tumor phenotype. Therefore, targeting the MDK-NCL axis emerges as a promising therapeutic avenue.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the MIF/CXCR4 pathway is considered crucial for the recruitment of mesenchymal stem cells 47 . Single-cell transcriptomic studies have demonstrated that tumor cells can also affect CAFs 48 and endothelial cells 49 through the MDK-NCL pathway, contributing to an immunosuppressive microenvironment. Signaling pathways associated with stemness play a significant role in systemic treatment resistance 50 .…”
Section: Discussionmentioning
confidence: 99%